Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/imm.12341
|View full text |Cite
|
Sign up to set email alerts
|

‘As above, so below’ examining the interplay between emotion and the immune system

Abstract: SummaryWhile the concept of a palpable relationship between our mental and physical well-being is certainly not new, it is only in the light of modern scientific research that we have begun to realize how deeply connected our emotional and immune states may be. We begin this review with a series of studies demonstrating how four fundamental emotional responses: anger, anxiety, mirth and relaxation are able modulate cytokine production and cellular responses to a variety of immune stimuli. These modulations are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 110 publications
2
39
0
4
Order By: Relevance
“…Several studies (9,22,28,37,38,95,118) have highlighted the link between emotion and immunity. Studies have shown how external conditions (massage-like stroking or enriched environment) can improve the host resilience to immunosuppression (89,118).…”
Section: Effect Of Emotional States On Os and Inflammationmentioning
confidence: 99%
“…Several studies (9,22,28,37,38,95,118) have highlighted the link between emotion and immunity. Studies have shown how external conditions (massage-like stroking or enriched environment) can improve the host resilience to immunosuppression (89,118).…”
Section: Effect Of Emotional States On Os and Inflammationmentioning
confidence: 99%
“…Especially in chronic illness, these factors have been shown to be associated with health outcomes (Brod, Rattazzi, Piras, D'Acquisto, 2014;Dragoş & Tănăsescu, 2010). In the field of psychoneuroimmunology, researchers focused on the bi-directional relationship between psychological and biological processes and evidence from the past decades indicates that psychological factors play a role with respect to illness progression.…”
Section: Positive Impact On Quality Of Lifementioning
confidence: 99%
“…Technically, psychological stress might be a form of chemical insult, but the specific chemicals have yet to be completely elucidated. Regardless, it has become increasingly apparent that stress and negative emotions can impact the functioning of the immune system (Brod et al, 2014). Maternal stress is a particularly dangerous insult because it is often not under the mother's control.…”
Section: Gestational Insultsmentioning
confidence: 99%